ICHTHYOFAUNAL DIVERSITY AND AQUACULTURE POTENTIAL OF SOME FLOODPLAIN WETLANDS IN THE DISTRICT OF NORTH 24 PARGANAS, WEST BENGAL - Mondal, Debjit Kumar; Das, Bipul Kumar; Kaviraj, Anilava (Journal of the Inland Fisheries Society of India, 2016)
Five floodplain wetlands, locally called ‘baor’, located in West Bengal were studied in the year 2003. Sixty species (including five exotic species) belonging to twenty-four families were recorded in the baors. Stocking and harvesting of carps is practiced in the baors on annual basis. Maximum yield (901.9 kg/ha) of carps was recorded from Gopalnagar baor during 2000-2001. The major carps are harvested during a specified season while the small fish are harvested throughout the year without any regulation. Gudusia chapra, Amblypharyngodon mola, Mystus sp. and Puntius sp. constitute a significant percentage of the total catch. A detailed account of ichthyofaunal diversity and aquaculture potential of the baors have been discusse